SURVEI ATAS IMPLEMENTASI GOOD UNIVERSITY GOVERNANCE Studi Kasus STAIN Pekalongan - Ahmad Rosyid; Agus Fakhrina; Miftahul Huda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2014)
The implementation of Good University Governance’s principles (accountability and responsiveness), academic culture, academic’s service quality and initiatives in the STAIN Pekalongan’sacademic society was tested in this study. Data werecollected from three main internal stakeholders (students, staffs, and lecturers) usingquestionnaire and their perception differences were analized using non parametric test of difference. The results show that (1) the total averages results placed between 7.34 to 9.89 which means that research variables were at a medium level (2) lecturers’ perceptions differ significantly from bothstaffs and students.